IMPLEMENTING AUTHENTIC AI ASSESSMENT IN TESOL: CHALLENGES AND RESEARCH DIRECTIONS - Dilnoza Usmanova (TADQIQOTLAR, 2025)
This article addresses the practical challenges of implementing authentic AI- enhanced language assessment in TESOL contexts. Drawing on a four-dimensional framework of authenticity, we identify key implementation barriers at technological, pedagogical, and institutional levels. We propose a research agenda to address these challenges and offer practical guidelines for TESOL practitioners navigating the integration of AI assessment tools. The article concludes with recommendations for interdisciplinary collaboration between language educators, AI developers, and assessment researchers.